Injection of Cerium Oxide Nanoparticles to Treat Spinal Cord Injury in Rats. Issue 8 (26th April 2022) - Behroozi, Zahra; Rahimi, Behnaz; Hamblin, Michael R; Nasirinezhad, Farinaz; Janzadeh, Atousa; Ramezani, Fatemeh
Abstract: This study investigated the effects of local injection of cerium oxide nanoparticles (CeONPs) in a rat spinal cord injury (SCI) model. Thirty-six adult male Wistar rats were divided into 4 groups: controls (healthy animals), sham (laminectomy), SCI (laminectomy+SCI induction), and treatment (laminectomy+SCI induction+intrathecal injection of CeONPs immediately after injury). SCI was induced using an aneurysm clip at the T12-T13 vertebral region. Motor performance and pain threshold tests were performed weekly; H&E staining and measurement of cavity sizes were performed 6 weeks after injury. The expression of granulocyte colony-stimulating factor (GCSF), P44/42 MAPK, P-P44/42 MAPK, Tau, myelin-associated glycoprotein(MAG) was evaluated after 6 weeks by Western blot. The Basso, Beattie, and Bresnahan locomotor scoring scales improved in animals receiving CeONPs compared with SCI animals. The cavity sizes were less in the treatment group. GCSF expression was similar in the animals receiving CeONPs compared with the SCI group but the expression of ERK1/ERK2 and phospho-ERK was lower than in the SCI group. Expression levels of Tau and MAG were significantly increased in treated animals compared to the SCI group. These data indicate that the use of CeONPs may improve motor functional recovery in SCI.